Analysis Of Grab Driver Partner Insurance Claim Procedure In Handling Driving Accidents - Ariski, Martogi; Anggraini, Tuti; Nurbaiti, Nurbaiti (UNIVERSITAS PAKUAN, 2025)
This study aims to analyze the insurance claim procedures provided by Grab for its driver partners in managing accidents and medical expenses. The focus of this research is to understand the actual procedure for filing claims, the obstacles encountered, and how this procedure helps drivers cope with the financial impact of accidents. A qualitative approach was used through in-depth interviews with several driver partners who have filed insurance claims. The findings show that although Grab's claim procedure is designed to be completed within a minimum of 1x24 hours with complete data, in reality, the process is often delayed due to additional requirements and inconsistencies in designated referral hospitals. These issues hinder the smooth handling of claims. Based on these findings, it is recommended that Grab improve socialization about the claim procedure, simplify the required documents, and reevaluate the referral system to ensure faster claim settlements. This research is expected to contribute to improving the effectiveness and practicality of insurance claim procedures for Grab driver partners in the ride-hailing industry.